A Parallel Robot with Torque Monitoring for Brachial Monoparesis Rehabilitation Tasks - Pisla, Doina; Tarnita, Daniela; Tucan, Paul; Tohanean, Nicoleta; Vaida, Calin; Geonea, Ionut Daniel; Bogdan, Gherman; Abrudan, Cristian; Carbone, Giuseppe; Plitea, Nicolae (Applied sciences, 2021)
Robots for rehabilitation tasks require a high degree of safety for the interaction with both the patients and for the operators. In particular, high safety is a stable and intuitive control of the moving elements of the system combined with an external system of sensors able to monitor the position of every aspect of the rehabilitation system (operator, robot, and patient) and overcome in a certain measure all the events that may occur during the robotic rehabilitation procedure. This paper presents the development of an internal torque monitoring system for ASPIRE. This is a parallel robot designed for shoulder rehabilitation, which enables the use of strategies towards developing a HRI (human–robot interaction) system for the therapy. A complete analysis regarding the components of the robotic system is carried out with the purpose of determining the dynamic behavior of the system. Next, the proposed torque monitoring system is developed with respect to the previously obtained data. Several experimental tests are performed using healthy subjects being equipped with a series of biomedical sensors with the purpose of validating the proposed torque monitoring strategy and, at the same time, to satisfy the degree of safety that is requested by the medical procedure.